2020
DOI: 10.1111/jfpp.14865
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure processing effects on the barrier properties of flexible packaging materials

Abstract: The aim of this research was to evaluate the influence of high-pressure processing on the barrier properties of flexible packaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The package properties calculation on the basis of the sorption parameters revealed that the increase in temperature led to an increase in the permeability of materials. Such variation may be attributed to differences in the structure and morphology of packaging films, as well as a dependence on temperature as reported by Marangoni et al 48 Furthermore, rise in temperature create more spaces in the polymeric structure of packaging material 20 and loosens the structure because of the greater mobility of molecules resulting in high permeability. Othman et al 49 postulated the similar effect of temperature variation on the permeability of film from potato peel.…”
Section: Discussionmentioning
confidence: 92%
“…The package properties calculation on the basis of the sorption parameters revealed that the increase in temperature led to an increase in the permeability of materials. Such variation may be attributed to differences in the structure and morphology of packaging films, as well as a dependence on temperature as reported by Marangoni et al 48 Furthermore, rise in temperature create more spaces in the polymeric structure of packaging material 20 and loosens the structure because of the greater mobility of molecules resulting in high permeability. Othman et al 49 postulated the similar effect of temperature variation on the permeability of film from potato peel.…”
Section: Discussionmentioning
confidence: 92%
“…O 2 and CO 2 ), so that there may be an increase in O 2 content inside the packaging medium with storage time, favouring the development of lipid oxidation. In the case of B‐2 and B‐3 fish, this effect could be more important on the basis that previous HPP has been reported to increase the permeability of most packaging materials throughout subsequent storage (Bull et al ., 2010; Marangoni Júnior et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In order to optimize preservation processes and minimize product handling, HPP is usually applied to previously packed food. The food packaging film could stand the strong mechanical force during HPP treatment (Marangoni Junior et al, 2020; Marangoni Júnior, Cristianini, Padula, & Anjos, 2019). Our previous studies have shown that the microstructure, barrier properties, and thermal properties of PLA/nano‐silver composite film could be improved after 200 MPa high pressure treatment (Fan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%